Compact four‐pole wideband bandpass filter with mixed electric and magnetic coupling. Issue 6 (8th February 2020) - Guan, Xuehui; Xie, Shuhai; Ren, Baoping; Li, Xiuping
Abstract: A wideband bandpass filter (BPF) based on two dual‐mode stub‐loaded stepped‐impedance resonators (SLSIRs) with mixed electric and magnetic coupling (MEMC) is proposed. Magnetic coupling is realized by using a transmission line, open end‐coupling and inter‐digital‐coupling provide a weak and a strong electric coupling, respectively. Due to the canceling effect of MEMCs, together with its harmonic effect, four transmission zeros (TZs) aside the passband are created and the selectivity of the filter is therefore highly improved. To verify the proposed design, a four‐pole wideband BPF operating at 3.35 GHz with 3 dB fractional bandwidth (FBW) of 32.96% is designed, fabricated, and measured. The measured minimum insertion loss is 0.95 dB, and the passband return loss is better than 11 dB.